Acoustic Properties of 316L Stainless Steel Hollow Sphere Composites Fabricated by Pressure Casting - Chunhe Wang; Fengchun Jiang; Shuaiqi Shao; Tianmiao Yu; Chunhuan Guo (Metals, 2020)
In this study, we prepared metal hollow sphere composites (MHSCs) using metal hollow spheres (MHSs) by pressure casting under vacuum conditions, and investigated the acoustic properties. The density of the MHSCs was measured using the mass to volume ratio, the microstructure of the MHSCs was observed using a scanning electron microscope, and the acoustic properties of the MHSCs were tested using an impedance tube. The measured MHSCs showed that the densities of the MHSCs with the random distribution of MHSs with diameter ~3.28 mm (1.74 g/cm3 to 1.77 g/cm3) (MHSC-3.28) were nearly equal to that of the MHSCs with the random distribution of MHSs with diameter ~5.76 mm (1.74 g/cm3 to 1.76 g/cm3) (MHSC-5.76), and lower than that of the MHSCs with the layered structure of MHSs with diameter ~3.28 mm (1.93 g/cm3 to 1.97 g/cm3) (MHSC-LS). Microstructural observations confirmed that the interface region between the MHSs and matrix demonstrated a simple physical combination pattern with pores. The acoustic properties of the MHSCs showed that the sound absorption coefficient of MHSC-LS was lower than that of MHSC-3.28 and higher than that of MHSC-5.76 at off-resonance. The sound absorption coefficient peak value of MHSC-3.28 was higher than that of MHSC-LS, and lower than that of MHSC-5.76 at resonance. The sound transmission loss of MHSC-3.28 was lower than that of MHSC-5.76, which shows the rules are independent from the resonance. The sound transmission loss of MHSC-LS was higher than that of MHSC-5.76 at resonance, but lower than that of MHSC-3.28 at off-resonance. In addition, we discuss the propagation mechanism of the sound waves in the MHSC, which is mainly determined by the distribution of the MHSs in the MHSC.